Teaching Vocabulary Using Games: Empowering Students' Interest in ELT Classrooms - Hasbi, Muhammad; Munawir, Ahmad; Satriani; Ahmad, Gufran; Khair, Ummul (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
The IAI As'adiyah Sengkang English education study program at the MTs As'Adiyah school performs community service. This practice is a kind of community service, particularly in schools, where it is used to carry out the commitments outlined in the Tridharma of higher education. The strategy aims to teach English vocabulary in the classroom using games. According to the results of PKM activities, students can more easily understand and remember vocabulary during the teaching and learning process, the effectiveness of teaching and learning activities can be monitored by the teacher, students can participate in learning with high enthusiasm, the material can be presented in an interesting manner by the teacher, and the topics in the material are also close to the students' daily lives. As a result of these activities, students become more interested in the learning process, which improves teacher-student communication.